Perancangan Interior Sentra Galeri dan Workshop Kerajinan Kayu di Blora, Jawa Tengah - Novia Christina; Sherly de Yong; Lucky Basuki (Intra, 2019)
Places or area that are not perfect to do production or buy and sell activities may reduce buyer’s interest. This wooden furniture comes from the root of waste which is no longer used and is processed and sold on the edge of the highway. With the interior design project of the gallery and workshop, it is expected to be able to help improve the economy of local community, especially the craftsmen. Another benefit gained is to increase the potential of locality, introduce soft and hard skills from the wood craftsmen, improve educational, recreational, interactive values for the community and reduce environmental problems. This design project used the Human Centered Design approach carried out from the traditional behavior of the local community in a natural context. This design process raises the design concept "Locana Wood" which consists of two meanings namely Localism and Naturalism. Localism is applied so that people feel the tradition of localization in the form of thoughts, systems, life philosophy and the values contained in it. In this case the local material is used in the design and human resources from local craftsmen. While Naturalism implemented by applying elements of nature and create designs to serve humans.